GADGETS, PARENTS AND CHILDREN: NAVIGATING THE DIGITAL LANDSCAPE IN FAMILIES - Norsiah Abdul Hamid; Sabrina Mohd Rashid; Mohd Fikri Yazan; Noor Azlina Amin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The rapid proliferation of digital technologies has significantly transformed the way individuals interact with the world around them. This digital revolution has also permeated the sphere of parenting, leading to a marked increase in the use of digital devices by both parents and children. While this shift has brought about numerous benefits, it has also raised concerns about potential negative consequences. This article highlights the research undertaken to understand the trends of digital usage among parents and children in Malaysia, by utilising a cross-sectional survey among parents who have 7-9 years old children using an online survey platform. A total of 532 parents responded to the survey and the data were analyse descriptively. This study found that many households own computers, tablets and smartphones, as compared to other devices such as smartwatch and digital game console. In addition, majority of the parents use digital devices between 3 to 5 hours and more than 5 hours daily, while many children use between 1 to 5 hours daily. Parents also use digital devices throughout the day, while children usage was reported higher during the weekend. Majority of the parents use digital devices for communication purpose, to search for information and to stay informed about current news, but most of the children use digital devices to fill free time, to complete school work and for entertainment purpose, but less use to get current news. Majority of the parents prefer WhatsApp, Facebook, TikTok and YouTube, while children prefer video-sharing and entertainment platforms namely YouTube, TikTok and online games. This study contributes to the enhancement of understanding of the trends in digital usage between parents and children.